Description of Alcyonohippolyte brachycarpus sp. nov., a further new hippolytid shrimp (Decapoda, Caridea, Hippolytidae) associated with soft coral from Taiwan, with the key to the species of the genus Alcyonohippolyte Marin, Okuno & Chan, 2011 - Marin, Ivan; Chan, Tin-Yam (Zootaxa, 2012)
A new species of soft coral associated hippolytid shrimp of the hippolytid shrimp genus Alcyonohippolyte Marin, Okuno& Chan, 2011 is described from northern Taiwan. The new species, Alcyonohippolyte brachycarpus sp. nov., inhabits softcoral “Sinularia sp.”, the same host as for A. maculata Marin, Okuno & Chan, 2011. At the same time, the new speciescan be easily separated from A. maculata by different coloration as well as having shorter carpal segments of pereiopodsII in females. Though occurring simpatrically, these two species have not yet been found inhabiting the same host together.The key for all known species of the genus Alcyonohippolyte is given based on morphology of females as no males have yet been known for the type species of the genus Alcyonohippolyte, A. dossena Marin, Okuno & Chan, 2010.